Liver transplantation for unresectable metastases from colon adenocarcinoma (2016)
Liver transplantation is an option that improves quality of life and prolongs life expectancy in patients with different types of liver disease. Liver transplantation is controversial for colorectal metastases and is not recommended in clinical practice guidelines. In this case report, we present, to our knowledge, the first liver transplantation for colorectal metastases conducted in Colombia, with a successful follow-up of more than 2 years. Patients with these characteristics who underwent liver transplantation experience reduced mortality and exponentially improved quality of life.